Complications following Suture Button Use for Femoral Graft Fixation in Arthroscopic Anterior Cruciate Ligament Reconstruction: A Systematic Review - Yassa, R.; Adam, J. R.; Charalambous, C. P. (The Journal of Knee Surgery, 2020)
Understanding any potential complications that may occur in relation to the use of a suture button for femoral graft fixation in arthroscopic anterior cruciate ligament reconstruction can help raise awareness among surgeons and improve safety when using such implants. This is a systematic review of suture button related complications. A literature search was conducted using the PubMed, Embase, and CINAHL (Cumulative Index to Nursing and Allied Health Literature) databases from their year of inception until January 3, 2019. We included studies reporting on suture button related complications in their outcomes of femoral graft suture button fixation in anterior cruciate ligament reconstruction. Our search identified 479 articles, of which 19 met our inclusion criteria. Suture button misplacement (initial or subsequent migration) was the most commonly reported complication. Although, in most cases, button misplacement is minimal and does not adversely affect clinical outcomes, in some cases it may lead to graft failure or local soft tissue irritation and require further surgery. Intraoperative screening or arthroscopic evaluation of the deployed suture button may reduce this complication.
Keywords: suture; button; anterior; cruciate; complication